If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(4 + -5x) = 42 (4 * 3 + -5x * 3) = 42 (12 + -15x) = 42 Solving 12 + -15x = 42 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -15x = 42 + -12 Combine like terms: 12 + -12 = 0 0 + -15x = 42 + -12 -15x = 42 + -12 Combine like terms: 42 + -12 = 30 -15x = 30 Divide each side by '-15'. x = -2 Simplifying x = -2
| 16=2p | | 60=2 | | 6x+21=6x+21 | | 42900+(0.2x)=x | | 3x=64-5x | | 25x+1=76 | | 2x+3x+x+60=180 | | 9h-16=h-2(2-3h) | | 28+x^2-11x= | | 1a+12=66.9 | | 1a+12=66.8 | | 72=9xd | | -2k+5=21 | | 3y-6=-21 | | R^2+35=12 | | A=3ab | | =-32 | | -13+2x=39+8x | | 61=4x-15 | | 0.14x+0.9(x-2)=0.01(4x-2) | | -2b+1=-17 | | 17x-3=82 | | 13x+45=19x+3 | | 7g+14-39=6 | | 6.5+9.5x=x+43.3 | | ax+6y=c | | 12p+39=500 | | 7.5a+11=93.5 | | -10+3(8+8y)=-6(y-4) | | 2+3k=-22 | | 2x-4=-32 | | 6x+15=x+15 |